PERANCANGAN SISTEM PEMESANAN DAN PENJUALAN BERBASIS ONLINE UNTUK APOTEK, STUDI KASUS APOTEK GUNA SEHAT JAKARTA - Nanang Husin (ESENSI: Jurnal Manajemen Bisnis, 2018)
In the information technology has developed, the existence of the current Internet is not only used as a dominant search of information, but as a business support media such as promotion, ordering and other uses. All of these activities are also supported various internet facilities as the ease of making website creation and social media blog that became a trend in the world today. The study aims to design information system online ordering Pharmacies in Jakarta by using online platform. This web-based information systems can provide convenience for customers to obtain information and conduct transactions.